2004
DOI: 10.1016/j.cardiores.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Decreased protein and phosphorylation level of the protein phosphatase inhibitor-1 in failing human hearts

Abstract: The results suggest that the reduction in I-1 protein and phosphorylation in failing human hearts leads to increased phosphatase activity which in turn may result in reduced phosphorylation of cardiac proteins such as PLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 25 publications
11
91
0
1
Order By: Relevance
“…7). Moreover, the PKA-dependent inhibitory regulator of PP1, inhibitor-1, reduced expression of which in failing ventricles has been suggested to contribute to reduced protein phosphorylation (20), was also not different between the two groups of cells.…”
Section: H387mentioning
confidence: 81%
“…7). Moreover, the PKA-dependent inhibitory regulator of PP1, inhibitor-1, reduced expression of which in failing ventricles has been suggested to contribute to reduced protein phosphorylation (20), was also not different between the two groups of cells.…”
Section: H387mentioning
confidence: 81%
“…Studies overexpressing constitutively active I-1c reported improved contractility and resistance to cardiac overload and ischemia/reperfusion injury (15,16). On the other hand, Ppp1r1a KO mice had essentially normal cardiac function and were partially protected from acute and chronic catecholamine toxicity (12). To dissect the specific roles of I-1 in normal and diseased conditions, we generated 2 mouse models that allowed investigation of the effects of conditional cardiac-specific expression of I-1c/ I-1 S67A on a Ppp1r1a KO background.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PKC-α phosphorylation at Ser67 attenuates I-1's inhibitory activity toward phosphatase-1, and this regulation of I-1 has been associated with depressed cardiac function in PKC-α transgenic mice (11). Notably, protein levels and PKA phosphorylation of I-1 were reduced in human failing hearts and were associated with decreased phosphorylation of PLB (12). Thus, I-1 downregulation likely participates in decreased SR Ca 2+ loading in failing myocytes.…”
Section: Introductionmentioning
confidence: 98%
“…It has been proposed that differential anchoring of PP1 to various compartments can explain differences between RyR2 and PLB phosphorylation in HF. 19 Moreover, it was shown that SR-associated PP1 activity is increased 2.5-fold, suggesting that I-1 preferentially localize to the SR. 28 El-Armouche et al found a good correlation between PLB and I-1 phosphorylation in human HF supporting the notification of a causal relationship and arguing for preferential affection of PLB (at the free SR) compared with the RyR2 located at the junctional SR. 29 Taken together, CaMKII-induced phosphorylation effects via PLB may be ameliorated, whereas phosphorylation of the RyR2 may be excessive in human heart failure. Thus, inhibition of CaMKII rather exerts effects on SR Ca 2ϩ release in HF similar to our finding of an improved SR Ca 2ϩ leak in human atrial fibrillating myocardium.…”
Section: Camentioning
confidence: 99%